Waterworks in a changing climate: the R.C. Harris filtration plant, Toronto, Canada. Issue 3 (5th June 2019) - Ross, Susan
Abstract : This research paper reviews the literature in an area of engineering heritage requiring further examination, the impact of climate change on historic urban water supply systems. Many opportunities exist to enhance the sustainability of historic waterworks still in operation in order to help mediate climate change effects. This must include mitigating climate change impacts on sources of potable water, such as by implementing strategies for water-efficient landscape design, while considering possible uses of the visible elements of the system, such as water treatment plants, to draw attention to this engineering heritage's continued and critical role. The R.C. Harris filtration plant is the main water treatment plant for the Greater Toronto Area in Canada, drawing water from Lake Ontario. This iconic 'Palace of Purification' has been in continuous use since 1941 and was declared a National Historic Civil Engineering Site in 1992. In 2013, it was still producing nearly 40% of Toronto's tap water. Examination of this plant serves to illustrate the interconnection of a system's historic design and its water source's watershed as heritage, to discuss expected impacts of climate change and explain not only some of the possibilities for mitigation, but also eventual necessary and challenging adaptations to changing treatment needs.